Qualitative evaluation of cardiac diagnostic machines in National Heart Institute of Malaysia / Dilkumar Marimuthu - Dilkumar, Marimuthu (2017)
Increasing number of cardiovascular disease (CVD) cases has been associated to a number of modifiable and non-modifiable risk factors. Echocardiogram, a commonly used diagnostic test for CVD, acquires the image of heart using ultrasound (high frequency sound waves). Thus, it is important to evaluate the different features of ultrasound machines methodically to ensure that the model selected for acquisition matches the user’s clinical practice requirements. The evaluation process applied in this research was aimed at choosing between Philips iE33 and GE Vivid E9 as the better cardiac ultrasound machine for future prospects by evaluating the image quality of Philips iE33 and Vivid E9 and performing a qualitative study of the image quality. This study involved 5 volunteers who consented for acquisition of basic images of echocardiography by both machines. The acquired images were then distributed to 50 respondents (doctors, medical officers and cardiovascular technologist) who took part in a questionnaire to express their preference for the machine(s). Results of questionnaire showed that physicians and technologist preferred Philips iE33 to Vivid E9, and Philips iE33 was found to produce better image quality as compared to GE Vivid E9.